Method of calculating the heat loss of an autonomous battery tank - Бердіғожа , А. О.; Жамалов, А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
There have been developedan algorithm and a program to determine the charging and discharging of the seasonal battery tank, considering the change in the water temperature in the battery tank and the average monthly ambient temperature during charging and considering the heat losses of the building during the battery discharge process. According to the calculations, there have been obtainedsatisfactory resultswhich confirm the possibility of using a seasonal accumulator tank to compensate for the heat losses of a building during the heating period.